The Stranski-Krastanov three dimensional island growth prediction on finite size model - Othaman, Zulkafli; Lim, Kheng Boo; Sakrani, Samsudi; Muhammad, Rosnita (Faculty of Science, 2008)
The Stranski-Krastanov growth theory is important to predict some of the nano-size semiconductor structures such as quantum dots and wires. This growth mode starts from a 2D thin film growth and transits into 3D island growth. The work done is to simulate and study the Stranski-Krastanov growth based on theoretical equations in energy changes. Three main energies involve are the chemical interaction energy, wetting energy and elastic energy. Parameters for various materials are used for the simulation and enable us to understand growth characteristics for certain material undergoing Stranski-Krastanov growth. The selected parameters are then used in actual growth conditions in the laboratory